A Survey on Multi Owner Data Sharing for Dynamic Groups in the Cloud Securely (International Journal of Engineering and Computer Science, 2016)
Cloud computing is the developing computer paradigm, where data owners can remotely store and modify their data on the premise of pay-as-use manner and enjoy on demand high-quality applications. The fundamental service provided by the Cloud is Data Storage which makes it a primary source for customers to utilize cloud for online data store and share. As it requires low maintenance it provides an economical and efficient solution for sharing group resource among cloud users .But, sharing  data  in  a  multi-owner  manner while  preserving  data  and  identity  privacy  from  an  untrusted cloud is still a challenging issue, due to the frequent change of the membership in the multi owner group. To preserve data privacy, a basic solution is to encrypt data files, and then upload the encrypted data into the cloud. Existing solutions usually apply cryptographic methods by disclosing data decryption keys only to authorized users which was a very tedious work. To resolve this problem recently the best efficient method MONA presented for secured multi owner data sharing for dynamic groups in the cloud has been proposed in which a group signature is used so that the revoked member is not able to upload or download files .By including  group  signature  and stateless  broadcast encryption techniques, any cloud user can anonymously share data with others .Meanwhile, the storage overhead, length of the signature and the running time of the signing algorithm are independent with the number of group members.